Locus of Control terhadap Kinerja Karyawan PT Jaya Makmur Indo Agro Usaha dengan Mediasi OCB - Rania Destiana; Ahmad Rizki Sridadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Employee performance is a crucial factor in achieving organizational objectives, particularly in the plantation sector, which requires accuracy, discipline, and teamwork. This study aims to examine the effect of locus of control (LOC) on employee performance and to test the role of organizational citizenship behavior (OCB) as a mediating variable at PT Jaya Makmur Indo Agro Usaha. The research employed a quantitative method with an explanatory design. The sample consisted of all 50 permanent employees, selected using a census technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that locus of control has a positive and significant effect on OCB and employee performance. In addition, OCB significantly influences performance and mediates the relationship between LOC and employee performance. These findings suggest that employees with a strong internal LOC are more likely to demonstrate voluntary work behaviors that enhance organizational effectiveness. Therefore, improving employee performance can be achieved through strengthening individual character and fostering a cooperative work environment.